2012
DOI: 10.1042/cs20110504
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2a receptor stimulation prevents hepatocyte lipotoxicity and non-alcoholic steatohepatitis (NASH) in rats

Abstract: NEFA (non-esterified 'free' fatty acid)-mediated lipotoxicity plays a critical role in the pathogenesis of NASH (non-alcoholic steatohepatitis). In the light of the growing need for new therapeutic options for NASH, we investigated the action of A2aR (adenosine A(2a) receptor) stimulation against lipotoxicity. The effects of the A(2a)R agonist CGS21680 [2-p-(2-carboxyethyl)phenethylamino-5'-N-ethylcarboxyamidoadenosine] were evaluated 'in vitro' in liver cells exposed to SA (stearic acid) and 'in vivo' in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 39 publications
4
47
0
Order By: Relevance
“…This feature allowed us to characterize the kinetic and the hepatic levels of different CD4 + T-cell subsets during the early phase of steatohepatitis development (first week), established steatohepatitis (second to fourth weeks) and evolution steatohepatitis/fibrosis (fourth to eighth week) as measured by ALT transaminase release, hepatic TG content, histological changes and pro-inflammatory/profibrotic cytokine content. In accordance with previous observations [26], the MCD diet induced a progressive increase in hepatic TG content ( Figure 1A) that paralleled the extension of steatosis ( Figure 1B). There was a significant increase in ALT release after just 1 week on the MCD diet, which peaked at the second week and remained significantly higher than that of mice receiving the ND (normal diet) at the fourth and eighth weeks ( Figure 1A).…”
Section: Th17 Cells Are Associated With Nash Initiationsupporting
confidence: 92%
See 1 more Smart Citation
“…This feature allowed us to characterize the kinetic and the hepatic levels of different CD4 + T-cell subsets during the early phase of steatohepatitis development (first week), established steatohepatitis (second to fourth weeks) and evolution steatohepatitis/fibrosis (fourth to eighth week) as measured by ALT transaminase release, hepatic TG content, histological changes and pro-inflammatory/profibrotic cytokine content. In accordance with previous observations [26], the MCD diet induced a progressive increase in hepatic TG content ( Figure 1A) that paralleled the extension of steatosis ( Figure 1B). There was a significant increase in ALT release after just 1 week on the MCD diet, which peaked at the second week and remained significantly higher than that of mice receiving the ND (normal diet) at the fourth and eighth weeks ( Figure 1A).…”
Section: Th17 Cells Are Associated With Nash Initiationsupporting
confidence: 92%
“…Hepatocytes were obtained by differential centrifugation at 50 g for 5 min at 4 • C. Hepatocyte suspensions (purity >95 %) were plated on collagen-coated culture dishes and cultured for 48 h in DMEM (Dulbecco's modified Eagle's medium)/Ham's F12 containing 10 % (v/v) FBS, 1 % penicillin/streptomycin and 1 % glutamine. For lipotoxicity assays [26], hepatocytes were incubated with fresh medium supplemented with 50 μmol/l PA (palmitic acid) (Sigma) in the presence or absence of 10 nmol/l recombinant murine IL-17 and or IL-22 (eBioscience).…”
Section: Isolation and Treatment Of Liver Cellsmentioning
confidence: 99%
“…GPCR activation leads to an elevation of cAMP (Hutchinson et al, 2008), which mediates apoptosis inhibition (Webster and Anwer, 1998;Kwon et al, 2004). The observed UDCA-LPE lipoprotection via cAMP/PKA signaling supports the possibility that UDCA-LPE may interact with specific GPCRs, among which are lipid-sensing GPCRs [e.g., sphingosine-1-phosphate receptor 2 (Studer et al, 2012) and adenosine A2a receptor (Imarisio et al, 2012)]. UDCA-LPE (or cAMP generated by UDCA-LPE) may interact with these GPCRs to induce PKA signaling leading to activation of cytoprotective signals Akt and ERK (Dent et al, 2005).…”
Section: Discussionmentioning
confidence: 60%
“…This suggests that the genomic changes induced by A2aR stimulation accomplish a full-protected phenotype only in presence of cell stress. Indeed, recent results showed that A2aR stimulation might also effectively prevent pathological conditions different from IR through the activation of noxious-specific mechanisms of protection [36].…”
Section: Discussionmentioning
confidence: 99%